The Study of the Solution to a Generalized KdV-mKdV Equation - Xiumei Lv; Tengwei Shao; Jiacheng Chen (Abstract and Applied Analysis)
A mathematical technique based on an auxiliary equation and the symbolic computation system Matlab is employed to investigate a generalized KdV-mKdV equation which possesses high-order nonlinear terms. Some new solutions including the Jacobi elliptic function solutions, the degenerated soliton-like solutions, and the triangle function solutions to the equation are obtained.